Injury of the superior labrum in overhead athletes - van der Hoeven, H. (Medicine and Science in Tennis, 2004)
This paper describes a specific type of injury, the 'SLAP lesion', which was first identified by Stephen Snyder (11). For the general population, the loosening of the biceps anchor represents about 3.9% of all shoulder injuries (11). In a specific population of overhead athletes, this figure has yet to be identified but it is likely to be considerably higher. This is due to the so-called 'thrower's dilemma' - athletes attempting to create maximal kinetic energy and the physiological biomechanical limits of their shoulder joint. During a throwing motion, the shoulder is subjected to forces that exceed physiological limits in an attempt to gain maximum ball speed. In order to generate as much energy as possible when the ball is released, the shoulder is placed in a position of maximum external rotation and this is why shoulder injuries are common in overhead athletes. The biomechanical, pathophysiological and clinical aspects are mentioned and possible treatment is explained. Conclusion: Overhead athletes are susceptible to shoulder injuries. The occurrence of a SLAP lesion is a sport specific injury, which is caused by repetitive maximal abduction and external rotation, and subsequently pathological changes in the biomechanical behaviour of the shoulder. This pathomechanism can be prevented by an appropriate regime, consisting of kinetic chain exercises, strengthening of the scapula stabilising muscles and regular stretching of the posterior capsular to prevent tightness. Once a SLAP lesion is present, operative treatment yields predictive, good results. A specific postoperative rehabilitation program is as important as the operative procedure itself, especially if the athlete is being treated for a recurrence of the shoulder injury.